Pendapatan Usahatani Selada Hidroponik pada Vheehidroponik di Kelurahan Airmadidi Atas Kecamatan Airmadidi Kabupaten Minahasa Utara - Ratumbuysang, Jhose Frans Andreas; Ngangi, Charles Reijnaldo; Sondakh, Mex Frans Lodwyk (AGRI-SOSIOEKONOMI, 2023)
This study aims to calculate the income of hydroponic lettuce farming on Vheehidroponics in Airmadidi Atas Village, Airmadidi District, North Minahasa Regency. This research was conducted from March to June 2023 in Airmadidi Atas Village, Airmadidi District, North Minahasa Regency. The data used in this study are primary data and secondary data. Primary data were obtained through interviews using questionnaires, while secondary data were obtained from journals and theses. The method of data analysis is quantitative to calculate the income of hydroponic lettuce farming on Vheehidroponics. The results showed that the revenue of hydroponic lettuce farming on Vheehidroponik was IDR3,800,000, while the total costs incurred in lettuce farming in 1 month were IDR782,197, the income of hydroponic lettuce farming on Vheehidroponik in Airmadidi Atas Village, Airmadidi District, North Regency was IDR3,017,803 for 1 month.